2008
DOI: 10.1089/apc.2008.0010
|View full text |Cite
|
Sign up to set email alerts
|

Review:Thromboses among HIV-Infected Patients during the Highly Active Antiretroviral Therapy Era

Abstract: Venous thrombotic events (VTEs) may occur at higher rates among HIV patients; some studies suggest that HAART may increase the risk for these potentially life-threatening events. We performed a retrospective study among HIV patients to evaluate the incidence and risk factors for VTEs during the HAART era. A literature review was performed examining VTEs in the pre-and post HAART eras. Seventeen (3.7%) of 465 HIV patients experienced a VTE. The overall incidence rate of deep VTEs among HIV positive persons was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(158 citation statements)
references
References 80 publications
6
150
2
Order By: Relevance
“…The risk of thrombosis, including deep vein thrombosis and pulmonary embolism, is increased in HIV1 individuals. 156,157 The mechanisms are not clear but may involve increased platelet activation, and with it broad inflammatory consequences. Studies using a primate simian immunodeficiency virus infection model have shown that platelets are activated early in infection, contributing to a drop in platelet count immediately following infection.…”
Section: Platelets and Infectious Diseasementioning
confidence: 99%
“…The risk of thrombosis, including deep vein thrombosis and pulmonary embolism, is increased in HIV1 individuals. 156,157 The mechanisms are not clear but may involve increased platelet activation, and with it broad inflammatory consequences. Studies using a primate simian immunodeficiency virus infection model have shown that platelets are activated early in infection, contributing to a drop in platelet count immediately following infection.…”
Section: Platelets and Infectious Diseasementioning
confidence: 99%
“…[1][2][3] The exact mechanism for this hypercoagulability is unknown, but may involve abnormal levels of antiphospholipid antibodies and anticoagulant proteins, monocyte overexpression of thromboplastin, concurrent malignancies, immobilization, and the administration of prothrombotic medications. [4][5][6] Confusing matters is the fact that abnormal levels of free protein S and antiphospholipid antibodies are common in HIV-infected individuals and are not necessarily associated with the development of thromboses.…”
mentioning
confidence: 99%
“…8 As Bibas et al correctly point out, ongoing oppor tunistic infections can further increase the risk of VTE in patients infected with HIV. 9 We agree that infections and inher ited thrombophilia might have a synergic…”
Section: Correspondencementioning
confidence: 90%